2001
DOI: 10.1097/00004647-200103000-00007
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 Antisense Treatment Prevents Induction of Tolerance to Focal Ischemia in the Rat Brain

Abstract: In the rat, 60 minutes of transient ischemia to the middle cerebral artery results in infarction of the caudate putamen. Ischemic preconditioning with 20 minutes of transient focal ischemia produced tolerance (attenuated infarction volume) to 60 minutes of subsequent focal ischemia administered three days, five days, or seven days later. Western blots from tolerant caudate putamen demonstrated increased bcl-2 expression, maximum at 3 days and persisting through 7 days. Immunocytochemical examination found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 33 publications
6
61
1
Order By: Relevance
“…After preconditioning, we observed an increase in Bcl-2 protein expression, consistent with other reports (Bossenmeyer-Pourie and Daval, 1998;Shimizu et al, 2001). It is of note that the time course for ischemic tolerance was shorter in the in vitro model (24 hours) compared with the in vivo model of ischemic tolerance (3 days).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After preconditioning, we observed an increase in Bcl-2 protein expression, consistent with other reports (Bossenmeyer-Pourie and Daval, 1998;Shimizu et al, 2001). It is of note that the time course for ischemic tolerance was shorter in the in vitro model (24 hours) compared with the in vivo model of ischemic tolerance (3 days).…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous reports (Bossenmeyer-Pourie and Daval, 1998;Shimizu et al, 2001), we detected an increase in Bcl-2 expression after 30-min MCAO and levels remained elevated for up to 72 hours ( Figure 2A). In comparison, after harmful ischemia (100-min, MCAO), there was no increase in Bcl-2 expression (not shown).…”
Section: Ischemic Preconditioning Reduces Neuronal Damage After Harmfsupporting
confidence: 93%
“…Although cerebral blood flow was not measured in the present study, no differences in blood flow have been reported in the tolerant regions between sham-operated and preconditioned animals before and during test focal ischemia (Barone et al, 1998;Chen et al, 1996;Shimizu et al, 2001). Similarly, a dose of diazoxide that showed neuroprotection against focal ischemia elicited no or minimal effects on cerebral blood flow during the ischemia , and 5HD pretreatment did not influence the blood flow and abolished the protective effects of diazoxide (Liu et al, 2002).…”
Section: Fig 2 Effects Of Ischemic Preconditioning (30-minute Middlcontrasting
confidence: 49%
“…Kato et al [45] showed that two minutes of bilateral carotid artery occlusion in gerbils produced an increase in Bcl-2 at 30 h and peaked at 96 h, suggesting that the expression of Bcl-2 is involved in ischemic preconditioning. In addition to this, in the study of Shimizu et al [46] , ischemic preconditioning for 20 min with transient focal ischemia produced ischemic tolerance (attenuated infarction volume). The results of Western blot analysis from tolerant caudate-putamen demonstrated an increase in Bcl-2 expression 3-7 days after preconditioning.…”
Section: Bcl-2 Proteinmentioning
confidence: 86%